Вы находитесь на странице: 1из 5

V 0

B 1

2

V (x) = αδ (x)

ρ −→ 0 A 2 = A 2

V (x) =

V 0 ,

0,

a/2 < x < a/2 |x| > a/2

V 0 V 0 < E < 0) E k = 2 κ 2

2m

2

2m ψ xx =

ψ xx = κ 2 ψ

κ = 2m|E| x < a/2

ψ I (x) = Ae κx + Ae κx

x → −∞ A = 0

ψ I (x) = Ae κx

κ

2

= |E| > 0

2

2m

a/2 < x < a/2 V (x) = V 0

2

2m ψ xx V 0 ψ =

ψ xx = k 2 ψ

ψ II (x) = B cos (kx) + C sin(kx)

k = 2m (V 0 − |E|)

x > a/2 V 0 = 0

ψ III (x) = De κx

κ

2 κ 2

2m

= |E| > 0

k 2 + κ 2 = 2mV 0

2

κik 2 = e 2ika

±e ika

κ+ik

C

= 0

D

= A

B

= 0

D = A

x = a

2

x =

2

a

A = Be aκ cos ka

2

2

tan ka = κ /k

2

A = Ce aκ sin ka

2

2

tan ka = k /κ

2

ξ ka/2

β 2 2mV 0 a 2 / 2

κa = β 2 ξ 2

tan ξ = β 2 1

2

ξ

tan ξ =

ξ ξ 2

β 2

ξ β V 0 = g 2 /2a a 0

ξ

= 2m 2

g 2

|E| a 2 mg 2 2 a

2

=tan ξ ξ mg 2 a

2

β 2 ξ 2

1 =

g 2 a/2

|E| a |E| a 2 2a |E|

2

g 2

|E| = mg 4

2

2

mV

2

2

2

0

a

2

a 0

2

ξ <

π

10

8

6

4

2

0.2 0.4 0.6 0.8 1.0 1.2 1.4 x
0.2
0.4
0.6
0.8
1.0
1.2
1.4
x